2015
DOI: 10.1007/s00394-015-0883-4
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit juice improves glucose intolerance in streptozotocin-induced diabetes by suppressing hepatic gluconeogenesis

Abstract: These findings show that GFJ is not insulinotropic but improves glucose intolerance in diabetic rats by suppressing hepatic gluconeogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…These observations confirm that naringin reversed metabolic acidosis associated with DKA albeit in experimental animal model. We recently reported antidiabetic effects of grapefruit juice in experimental animal studies [ 30 ]. Naringin is the main flavonoid in grapefruit juice and therefore it seems plausible to infer that some of the antidiabetic effects of grapefruit juice could be attributed to naringin in addition to other as yet unidentified bioactive chemical ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…These observations confirm that naringin reversed metabolic acidosis associated with DKA albeit in experimental animal model. We recently reported antidiabetic effects of grapefruit juice in experimental animal studies [ 30 ]. Naringin is the main flavonoid in grapefruit juice and therefore it seems plausible to infer that some of the antidiabetic effects of grapefruit juice could be attributed to naringin in addition to other as yet unidentified bioactive chemical ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, naringin treatment significantly improved glucose tolerance not only in normal but also in PI-exposed rats compared to the control and PI-treated rats, respectively ( Fig 4B ). Antihyperglycemic effects of naringin have previously been described [ 25 , 26 ]. In our study, naringin treatment significantly increased glucokinase protein content in both hepatic and pancreatic tissue compared to either controls or ATV- or SQV-treated animals, respectively ( Fig 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Naringin is a flavanone derived from citrus species and has been demonstrated to possess antioxidant, anti-diabetic, anti-dyslipidemic and anti-inflammatory activities [ 22 24 ]. Hypoglycemic effects of naringin have previously been demonstrated [ 25 , 26 ]. We have recently reported that naringin improves both glucose intolerance and insulin resistance in non-diabetic rats [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Areca nut extract enriched with catechin‐based procyanidins reduced the level of hepatic G6Pase mRNA in STZ‐treated mice . Grapefruit juice has been reported to improve glucose intolerance in STZ‐treated rats by suppressing hepatic gluconeogenesis . Because azuki beans have previously been reported to be rich in proanthocyanidins as well as other catechins, it is possible that ABE treatment may suppress hepatic gluconeogenesis by reducing G6Pase protein expression via AMPK activation.…”
Section: Discussionmentioning
confidence: 99%